Two men and oxen on Skagway Trail, 1898 - Curtis, Asahel, 1874-1941
In 1897 and 1898, some of the Klondike stampeders used oxen to carry supplies along the White Pass Trail. Others used dogs, horses, mules, and even goats. Once the railroad was completed from Skagway through White Pass, there was less need for these pack animals. In this 1898 photo taken by Asahel Curtis, two men stand in the snow near their ox-drawn sleds. Original photo in "Klondike Rush of '98" Photograph Album, 2010.3.14. 1 photographic print: b&w; 5 x 7 in.